Analysis of solvency capacity of Algerian insurance companies in retaining underwriting risks - Boumakhlouf, Abdenour; Aid, Lamine (International journal of economic perspectives, 2025)
This study aims to assess the financial solvency of Algerian insurance companies and their ability to retain the revenue generated from underwriting risks by examining retention and cession rates and analyzing the impact of financial solvency on their risk coverage capacity. Insurance companies in Algeria rely heavily on reinsurance as a key mechanism to manage risks, transferring a portion of risks that exceed their financial capacity. This practice often results in the cession of a significant portion of their revenue in certain cases. The study analyzes data from insurance companies operating in the market, including both general insurance and life insurance companies, during the period from 2018 to 2022. The research focuses on evaluating their financial solvency, comparing retention and cession rates, and benchmarking against industry standards derived from market data. The findings reveal that six companies struggle with low-risk retention capacity, four of which are due to weak financial solvency, while two face challenges from other factors. The study recommends strengthening the financial solvency of companies with low retention rates by increasing capital and reserves, improving reinsurance strategies, and adopting co-insurance mechanisms to reduce dependence on external reinsurance.